2019
DOI: 10.1186/s12888-019-2018-6
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of cognitive remediation for a national cohort of forensic patients with schizophrenia or schizoaffective disorder

Abstract: BackgroundEvidence is accumulating that Cognitive Remediation Training (CRT) is effective for ameliorating cognitive deficits experienced by patients with schizophrenia and accompanying functional impairment. There has been no randomized controlled trial of CRT using a nationally representative population of forensic patients, despite the significant cognitive deficits frequently present within this group.MethodsSixty-five patients with schizophrenia or schizoaffective disorder were enrolled in a single blind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…Moreover, BDNF concentration positively correlated with cognitive performance in a RBANS scale of memory. Not only the pharmacological interventions were effective on the reduction of mnemonic symptoms, different cognitive training protocols were also designed to enhance specific cognitive domains, especially memory (Guimond et al, 2018; O’Reilly et al, 2019). Fisher et al (2016) conducted a computerized cognitive training in SZ patients and the patients exposed to this program present higher levels of sBDNF compared to the control group.…”
Section: Psychiatric Disorders and Bdnfmentioning
confidence: 99%
“…Moreover, BDNF concentration positively correlated with cognitive performance in a RBANS scale of memory. Not only the pharmacological interventions were effective on the reduction of mnemonic symptoms, different cognitive training protocols were also designed to enhance specific cognitive domains, especially memory (Guimond et al, 2018; O’Reilly et al, 2019). Fisher et al (2016) conducted a computerized cognitive training in SZ patients and the patients exposed to this program present higher levels of sBDNF compared to the control group.…”
Section: Psychiatric Disorders and Bdnfmentioning
confidence: 99%
“…As the field continues to grow, with several treatment programs available, health care decision makers who wish to bring cognitive remediation to the clinic should be encouraged that, although this treatment requires training and staff time, the cost‐benefit analysis is favorable. Studies of cognitive remediation have systematically reported on how this trade‐off affects quality of life and financial burden associated with cognitive impairment, with evidence supporting higher rates of employment, reduced job stress, and lower institutional treatment demands.…”
mentioning
confidence: 99%
“…40 Cognitive rehabilitation has been utilized to treat neurocognitive and neurodevelopmental disorders to increase functioning. In a study of cognitive rehabilitation in forensic patients, O'Reilly and colleagues 41 supported the use of cognitive rehabilitation interventions to improve several cognitive functions and reduce risk (eg, moved to lower security unit). Persons with schizophrenia often display social deficits.…”
Section: Treatment To Address Violence Riskmentioning
confidence: 99%